Implementasi Digital Marketing dalam Peningkatan Kredibilitas dan Kapabilitas Usaha Jasa Pemberantas Hama (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
This community service activity is carried out to improve product management and marketing for MSMEs providing pest control services. The community service activity uses a descriptive qualitative method. The community service activity was carried out at the Cikamp Pest MSME located in Sambi Bulu Village, Taman, Sidoarjo which has been established since 2019. The community service implementation methods used include socialization, discussion, and mentoring methods. The community service activities carried out on Cikamp Pest MSME partners have a positive impact on partners through the programs offered, including promotions using digital methods including re-branding the Cikamp Pest logo, creating a Facebook page, main website, and YouTube channel to expand the marketing network so that more people know about the pest control service products owned by Cikamp Pest.